2005
DOI: 10.1103/physrevb.72.054109
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the optical transitions ofFcenters in the bulk and on the (0001) surface ofαAl2O3

Abstract: The electronic structure and spectroscopic features of the optical spectra of oxygen vacancies in the bulk and on the ͑0001͒ surface of ␣-Al 2 O 3 have been studied by first-principles methods. The effect of oxygen vacancies on the crystalline structure has been determined by the appropriate atomic structure optimization carried out using a periodic model and density functional theory ͑DFT͒ calculations. Both, neutral ͑F center͒ and charged ͑F + center͒ oxygen vacancies have been considered. Optical transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 71 publications
(84 reference statements)
2
32
0
Order By: Relevance
“…(This difference shows noticeable dependence of results on hidden DFT parameters, while using the same periodic model.) The periodic DFT‐B3LYP calculations give 8.5 eV 110, whereas both the TD‐DFT embedded cluster calculations 104 and semi‐empirical INDO cluster calculations 105 overestimate this value: 9.9 and 10.1 eV, respectively.…”
Section: Defects In Binary Oxides Of Light Metalsmentioning
confidence: 91%
See 1 more Smart Citation
“…(This difference shows noticeable dependence of results on hidden DFT parameters, while using the same periodic model.) The periodic DFT‐B3LYP calculations give 8.5 eV 110, whereas both the TD‐DFT embedded cluster calculations 104 and semi‐empirical INDO cluster calculations 105 overestimate this value: 9.9 and 10.1 eV, respectively.…”
Section: Defects In Binary Oxides Of Light Metalsmentioning
confidence: 91%
“…Unlike alkali halides and alkali earth oxides, creation of the F center in corundum crystal results in a substantial lowering of a local symmetry ( D 3italicd6→C 2 ). Probably, the noticeably smaller number of theoretical simulations on oxygen vacancies in α‐Al 2 O 3 3, 7, 9, 10, 100–106 may be explained by this low‐symmetrical structure and, thus, complexity of calculations required significant computational time and resources as well as interpretation of their results 102. The following methods and models were used for the F center studies in corundum: (i) periodic DFT calculations 9, 10, 100–104; (ii) time‐dependent (TD) DFT calculations on embedded clusters 7, 104 using the GAUSSIAN code 107; (iii) semi‐empirical embedded 3, 105 and cyclic 9, 106 cluster calculations by the INDO and MSINDO methods, respectively.…”
Section: Defects In Binary Oxides Of Light Metalsmentioning
confidence: 99%
“…In ionic oxides, the ground state of the F center involves two electrons well localized in the vacancy giving rise to energy levels in the band gap region with typical optical absorption around 5 -6 eV. 7,[20][21][22][23] For perovskite oxides such as SrTiO 3 , the electronic structure of the F-type defects is a subject of a long debate. 24 Several theoretical studies have suggested major and identical contributions from the 3d orbitals of the two Ti ions on both sides of O vacancy to the electron density of the F center, 13,19,26 although others indicate a partial or total localization of the electrons in the vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…For the terrace site we also carried out Time Dependent DFT calculations to obtain the transition energies to the lowest electronic states. This method has proven to be able to describe excitations of bulk and surface color centers of both MgO [33] and Al 2 O 3 [45]. However, in the TD-DFT calculations it is not possible to directly compute the excitations of interest and to reach them it is often necessary to include an exceedingly large number of states with nearly vanishing oscillator strength and, hence, very low transition probabilities.…”
Section: Materials Model and Computational Aspectsmentioning
confidence: 98%